Patient satisfaction with the behavioral competencies of their treating doctors: a hospital based study - Rajak, Kripa; Pandey, Shikha; Shah, Komal; Malla, Monisma (Journal of Patan Academy of Health Sciences, 2018)
Introductions: Patient satisfaction surveys are essential in identifying gaps in providing health care to patients and developing an effective plan for its quality improvement. This study aimed to assess the level of patient’s satisfaction with doctors’ behavioral competencies in communication skills, interpersonal manner, confidentiality maintenance and general satisfaction. Methods: A cross-sectional study was conducted in admitted patients of Department of Surgery, Orthopaedics, Internal Medicine and Obstetrics Gynaecology between August 4, 2015 and August 28, 2015. Samples were selected by stratified random sampling technique. They were interviewed using a validated tool in 7-point Likert scale and collected data were analysed using SPSS. Results: Out of 101 respondents, percentage of patients who had very high, high, medium, low overall satisfaction (communication skills, interpersonal manner, confidentiality maintenance and general satisfaction) were 27.7% (28), 24.8% (25), 20.8% (21) and 26.7% (27) respectively. Pearson Chi-square test and Mann-Whitney U test showed level of satisfaction did not differ with age, gender and educational level of respondents. There was positive Spearman’s rank correlation of general satisfaction with communication skill, confidentiality maintained and interpersonal manners. Communication skill had the highest correlation coefficient (57.8%). Conclusions: The overall satisfaction (very high and high satisfaction) of the patient with the behavioral competencies of doctors at Patan Hospital is 52.5%. Communication skill had the highest degree of influence on the level of patient satisfaction. The level of satisfaction was not affected by age, gender and educational level of patients.